Reaching for the Vulnerables: Assessing the Impact of Digital Financial Inclusion to the MSME Household’s Vulnerability to Poverty - Gilbert; Pricilia Meidy Winengko; Adho Adinegoro (East Java Economic Journal, 2020)
The COVID-19 pandemic has affected most parts of society, one of which is the MSME household. Although various assistance has been addressed to this sector in the short term, a long-term strategy through digital financial inclusion is needed to reduce the vulnerability of MSME households to falling into poverty in the long term. Using data from the Indonesian Family Life Survey 2014, this study investigates the impact of digital finan-cial inclusion on the vulnerability of MSME households in Indonesia and in East Java. The OLS and 2SLS analysis shows that digital financial inclusion helped reduce the poverty vulnerability of MSME households significantly. Further logistic regression analysis also shows that the reduction of poverty vulnerability occurred both in the risk-induced and structural vulnerabilities. Based on the findings, this study recommends policy stakeholders to formulate a digital financial inclusion strategy as one of the alternative policies for poverty alleviation in Indonesia.